Detection of Mycobacterium Tuberculosis Complex in Several Clinical Samples By Pcr - Toraman, Zülal Aşcı; Bulut, Yasemin; Özdarandeli, Aykut (Fırat University, 2002)
Aim: The aim of this study was to detect Mycobacterium tuberculosis in several clinical samples. The clinical samples were stained with Erlich-Ziehl-Neelsen (EZN) method. Then were subjected to polymerase chain reaction (PCR) using the primers specific to IS6110 region of Mycobacterium tuberculosis Material and Methods: In this study, a total of 116 cases (77 samples were cerebrospinal fluid, 13 samples were early morning gastric juice, 10 samples were urine, 5 samples were pleural fluid, and 6 samples were tracheal fluid) suspected with Mycobacterium tuberculosis infection were studied over 15 months. All samples were stained with EZN method and were subjected to microscobic examination. Thereafter PCR was applied to the samples to determine the presence of Mycobacterium tuberculosis complex. Results: Fifteen samples (12.3%) were positive when the samples stained with EZN method. However, fourty three samples (34.7%) appeared to be positive after PCR. Conclusion: Our results indicated that PCR is more sensitive than Ehrlich-Ziehl-Neelseen staining method. PCR is fast, simple and reliable method to detect Mycobacterum tuberculosis in several clinical samples.

Amaç: Bu çalışmada, ilk olarak asido-rezistan boyama (ARB) yöntemlerinden biri olan Erlich-Ziehl-Neelsen boyama yapılan çeşitli klinik örneklerde, IS6110 bölgesine spesifik primerlerin kullanıldığı Polimeraz Zincir Reaksiyon (PZR) yöntemiyle de Mycobacterium tuberculozis kompleksinin hızlı ve çabuk bir şekilde tespiti amaçlanmıştır. Gereç ve Yöntem: Çalışmada tüberküloz olduğu düşünülen 116 hastadan alınan 77'si beyin omurilik sıvısı (BOS), 13'ü açlık mide sıvısı (AMS), 10'u idrar, 10'u balgam, 5'i torasentez mayi ve 6'sı pleural mayiden oluşan 121 örnek kullanılmıştır. Bu örneklerin hepsi, dekontaminasyon ve homojenizasyon işlemi uygulandıktan sonra, ilk olarak Erlich-Ziehl- Neelsen (EZN) yöntemiyle boyanmış ve mikroskopta incelenmiştir. Aynı çalışmada, bütün örneklerde PZR yöntemiyle de Mycobacterium tuberculosis kompleksinin varlığı araştırılmıştır. Bulgular: Toplam 121 örneğin 15'in de ARB pozitif (% 12.3) bulunurken, PZR yöntemiyle ise 121 örneğin 42'ünde (% 34.7) Mycobacterium tuberculosis kompleksi pozitif olarak belirlenmiştir. Sonuç: Bu çalışmanın sonuçlarına göre, klinik örneklerlerden PZR yöntemiyle hızlı ve duyarlı bir şekilde Mycobacterium tuberculosis kompleksi belirlenmesi önerilmektedir.
Çeşitli Klinik Örneklerden Mycobacterium Tuberculosis Kompleks'in Polimeraz Zincir Reaksiyonuyla Belirlenmesi